DESIGN OF CHOKELESS WELDING TRANSFORMER WITH LOAD SERIES MOTOR - S. R. Shete; Prof. A. R. THorat (International Journal of Innovations in Engineering Research and Technology, 2021)
the forced area cooled welding transformer are conventially provided with fractional hores power single phase morter of shaded pole type. the fan are running as soom as the transformer is swithched on.